IMPLEMENTASI PROGRAM RASKIN UNTUK MEMBANTU PEREKONOMIAN MASYARAKAT MISKIN DI KECAMATAN TANAH MASA KABUPATEN NIAS SELATAN - Ingati Gowasa (PERSPEKTIF, 2016)
This qualitative research with the descriptive-analitical approach, explain and depict as complete as possible a circumstance going into effect in society. The technique to have the informan utilized in this research is purposive sampling by taking sample in Baluta Village, Hale Baluta Village, Hiliomasio Village and Bawo Ofuloa Village of Subdistrict Tanah Masa at Nias Selatan Regency. Result of this research is to indicate that the limited time of planning phase cause Rice for Poor Program impress "forced". The time limitation was influence the execution efficacy each step and overall of program. In goals meet the existence of misstargeting though in storey. This matter indication from existence of domestic is leakage and undercoverage.